Helicobacter Pylori infection in systemic sclerosis and its association with upper gastrointestinal dysfunction - Chilukuri Balaji; Mahendran Bhuvanesh; Chinnadurai Saranya; Ramamoorthy Ramesh; Mayilsamy Saravanan; Sankaralingam Rajeswari (Indian Journal of Rheumatology)
Background: Immune dysregulation triggered by environmental events (including microbes) have been implicated in the etiopathogenesis of systemic sclerosis (SSc). Helicobacter pylori (H. pylori) a pathogen well known to cause gastric ulcers and has been associated with several autoimmune diseases. However, the role of H. pylori in SSc has not been widely reported. The objective of the study was to estimate the prevalence of H. pylori infection in SSc patients and analyze its clinical associations. Methods: This study comprised 55 patients who satisfied ACR/EULAR 2013 classification criteria for SSc and 25 age and sex-matched healthy controls. Demographic, clinical, laboratory, and immunological parameters were recorded. Upper gastrointestinal (GI) endoscopy was done. Anti-H. pylori IgG levels (RU/ml) were estimated by ELISA and results analyzed by SPSS. Results: Baseline characteristics were comparable in both groups. Prevalence of H. pylori infection was high in SSc patients in comparison to controls (61.8% vs. 24%). Anti-H. pylori IgG levels were high in SSc patients in comparison to controls (mean 65 RU/ml vs. 25.3RU/ml; P = 0.003). SSc patients with symptomatic GI involvement had higher anti-H. pylori IgG levels than asymptomatic patients (mean 118.3 RU/ml vs. 20.7 RU/ml; P < 0.001). Anti-H. pylori IgG levels were not significantly different between diffuse cutaneous SSc and limited cutaneous SSc (mean 72.9 RU/ml vs. 54.1RU/ml; P = 0.289). Anti-H. pylori IgG antibody levels showed no correlation with disease duration, erythrocyte sedimentation rate, C-reactive protein, interstitial lung disease, and modified Rodnan Skin Score. Conclusion: SSc patients have high seropositivity for anti-H. pylori IgG antibodies. High anti-H. pylori IgG antibody titers are associated with symptomatic upper GI dysfunction.